2017
DOI: 10.1038/s41598-017-08421-z
|View full text |Cite|
|
Sign up to set email alerts
|

Fine Structure of Posterior Alpha Rhythm in Human EEG: Frequency Components, Their Cortical Sources, and Temporal Behavior

Abstract: Heterogeneity of the posterior alpha rhythm (AR) is a widely assumed but rarely tested phenomenon. We decomposed the posterior AR in the cortical source space with a 3-way PARAFAC technique, taking into account the spatial, frequency, and temporal aspects of mid-density EEG. We found a multicomponent AR structure in 90% of a group of 29 healthy adults. The typical resting-state structure consisted of a high-frequency occipito-parietal component of the AR (ARC1) and a low-frequency occipito-temporal component (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 56 publications
10
55
0
2
Order By: Relevance
“…Also note that the EEG is likely dominated by a strong parieto‐occipital alpha generator. However, recent research suggests more than one concurrent alpha rhythmic “mode” involved in visual processing (Barzegaran, Vildavski, & Knyazeva, ; Keitel & Gross, ). It is therefore possible that our stimulation failed to influence the dominant rhythm but affected a less prominent alpha component that is more difficult to observe given the sparse spatial resolution of EEG recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Also note that the EEG is likely dominated by a strong parieto‐occipital alpha generator. However, recent research suggests more than one concurrent alpha rhythmic “mode” involved in visual processing (Barzegaran, Vildavski, & Knyazeva, ; Keitel & Gross, ). It is therefore possible that our stimulation failed to influence the dominant rhythm but affected a less prominent alpha component that is more difficult to observe given the sparse spatial resolution of EEG recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Also note that the EEG is likely dominated by a strong parieto-occipital alpha generator. However recent research suggests more than one concurrent alpha rhythmic 'mode' involved in visual processing (Keitel & Gross, 2016;Barzegaran et al, 2017). It is therefore possible that our stimulation failed to influence the dominant rhythm but affected a less prominent alpha component that is more difficult to observe given the sparse spatial resolution of EEG recordings.…”
Section: No Evidence For Entrainment Of the Intrinsic Visual Alpha Rhmentioning
confidence: 91%
“…Though it remains unclear how essential this alignment of the external and internal oscillator is (Notbohm and Herrmann, 2016;Reato et al, 2013), systematic shifts in peak frequency of the magnitude observed here may be important to consider when attempting to interact with ongoing activity. By contrast, the heterogeneous nature of the sources of alpha activity (Barzegaran et al, 2017;Bollimunta et al, 2008;Buffalo et al, 2011;Capilla et al, 2012;Haegens et al, 2015;Hughes and Crunelli, 2005;Katayama et al, 2011;Keitel and Gross, 2016b;Sadaghiani et al, 2010;Scheeringa et al, 2016) invalidates the assumption that the peak-frequency necessarily represents a single endogenous 'oscillator' and hence raises questions regarding the rationale of targeting the peak-frequency for entrainment. Therefore, precise targeting of oscillatory networks will benefit from more refined considerations of the origin and functional roles of the frequency and power content of the EEG signal.…”
Section: Methodological and Applied Considerationsmentioning
confidence: 99%
“…In order to further investigate the relative independence of the power increases and frequency decreases over time, we performed an analysis using independent component analysis (ICA) and current-dipole modelling to statistically separate sources of alpha-activity contributing to the EEG signal measured on the scalp. Scalp-level EEG alpha activity reflects a superposition of multiple alpha rhythms (Barzegaran et al, 2017;Keitel and Gross, 2016a).…”
Section: Alpha-band Source Separation Using Independent Component Anamentioning
confidence: 99%
See 1 more Smart Citation